Kebijakan Kriminalisasi LGBT Malawi Di Tengah Pengaruh Kelompok Kepentingan dan Politik Bantuan Luar Negeri - Puguh Toko Arisanto; Tiffany Setyo Pratiwi (Parahyangan Center for International Studies, 2020)
Issues of LGBT boomed in Malawi in 2009 after an arrest of homosexual couple who held a wedding party. The criminalization was based on the Malawi’s Penal Code. In 2010, Malawian government also added an article on the Penal Code to criminalize lesbians. However, after the succession of Malawi President in 2012, the successor president, Joyce Banda suspended the policy criminalizing LGBT to await a review of the Parliament. Amid the suspension, under a different President, on April 2015 Malawi passed an LGBT Act of criminalization through Marriage, Divorce and Family Relations Act. The authors note that there had been an inconsistency of the Malawi government in applying policy criminalizing LGBT. The government implemented the policy of criminalization towards LGBT based on Malawi Penal Code, suspended it in 2012, and then 2015 re-issued policy criminalizing LGBT through certain act. This article explores the roles of conflicting interest groups between religious leaders (RLs) and domestic NGOs followed by politics “stick and carrot” on foreign aid of donor states in Malawi. These variables are subjects to analysis that affect the inconsistency of Malawi government to implement policy criminalizing LGBT.Keywords: Criminalizing LGBT, Penal Code, Inconsistency, Conflicting Interest Groups, Stick and Carrot AbstrakIsu LGBT mulai menggelegar di Malawi pada tahun 2009 pasca penangkapan pasangan homoseks yang tertangkap mengadakan pernikahan. Kriminalisasi didasarkan pada pasal-pasal di KUHP Malawi. Tahun 2010, pemerintah Malawi juga menambah pasal di KUHP untuk menkriminalisasi lesbian. Namun pasca bergantinya Presiden tahun 2012, Presiden pengganti, Joyce Banda menangguhkan kebijakan kriminalisasi pelaku LGBT untuk menunggu review dari Parlemen. Ditengah pengangguhan, tahun 2015, di bawah Presiden yang berbeda, Malawi mengeluarkan UU kriminalisasi pelaku LGBT melalui Marriage, Divorce and Family Relations Act. Penulis melihat bahwa terjadi inkonsistensi pemerintah Malawi dalam menerapkan kebijakan kriminalisasi LGBT. Pemerintah Malawi menerapkan kebijakan kriminalisasi LGBT berdasarkan KUHP Malawi, tahun 2012 menangguhkannya, dan kemudian 2015 kembali mengeluarkan kebijakan kriminalisasi LGBT melalui UU. Artikel ini hendak memaparkan peran kelompok kepentingan yang saling bertentangan (conflicting interest groups) antara religious leaders (RLs) dan NGOs domestik beserta politik “stick and carrot” dalam bantuan luar negeri negara-negara pedonor di Malawi. Variabel-variabel tersebut menjadi pokok analisis yang mempengaruhi inkonsistensi penerapan kebijakan kriminalisasi LGBT di Malawi.Kata Kunci : Kriminalisasi LGBT, KUHP Malawi, Inkonsistensi, Conflicting Interest Groups, Stick and Carrot